Modelling of the cylindrical geometry cooling process based on the solution of the inverse problem - Joachimiak Magda (EDP Sciences, 2021)
Processes of thermo-chemical treatment, such as nitriding, are used to create a surface layer of high mechanical values. When the nitriding process, often consisting of a multi-stage heating and soaking, is ended, elements being under treatment are cooled. The cooling rate depends on the massiveness and geometry of the given element. Too fast cooling can result in the formation of high temperature gradients, which leads to the element damage. This paper presents numerical analysis of a cylinder cooling. The non-linear, unsteady inverse problem for the heat equation was solved. Test examples were chosen based on experimental research conducted in the furnace for thermo-chemical treatment.